2010
DOI: 10.1128/jvi.00831-10
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus Type 16 E5 Oncoprotein Inhibits Epidermal Growth Factor Trafficking Independently of Endosome Acidification

Abstract: The human papillomavirus type 16 E5 oncoprotein (16E5) enhances acute, ligand-dependent activation of the epidermal growth factor receptor (EGFR) and concomitantly alkalinizes endosomes, presumably by binding to the 16-kDa "c" subunit of the V-ATPase proton pump (16K) and inhibiting V-ATPase function. However, the relationship between 16K binding, endosome alkalinization, and altered EGFR signaling remains unclear. Using an antibody that we generated against 16K, we found that 16E5 associated with only a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 60 publications
2
56
0
Order By: Relevance
“…For instance, compared with the E1^E4 message ( Table 1, species a), the E5 transcript (Table 1, species b) is relatively minor. This finding is in accordance with our understanding that E5 is a signal transduction regulatory protein (41), whereas E1E4 is an abundant cytoplasmic protein that interacts with cytokeratins (42). Interestingly, the E6 F4L mutant and the WT virus were virtually indistinguishable in abundance of each of the RNA species, whereas the other mutants had significantly reduced RNA levels (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, compared with the E1^E4 message ( Table 1, species a), the E5 transcript (Table 1, species b) is relatively minor. This finding is in accordance with our understanding that E5 is a signal transduction regulatory protein (41), whereas E1E4 is an abundant cytoplasmic protein that interacts with cytokeratins (42). Interestingly, the E6 F4L mutant and the WT virus were virtually indistinguishable in abundance of each of the RNA species, whereas the other mutants had significantly reduced RNA levels (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The oncogenic role of HPV16 E5 in epithelial transformation and malignant progression has been widely attributed to the ability of this viral protein to interfere with the endocytic pathway of signaling receptors, mainly of EGFR, either indirectly through inhibition of the endosomal acidification (Straight et al, 1995) and endosomal vesicle fusion (Suprynowicz et al, 2010), or directly through protein interactions with the receptor tyrosine kinases (Hwang et al, 1995;Zhang et al, 2005). As mentioned above, results obtained in previous studies from our group (Belleudi et al, 2006(Belleudi et al, , 2007 demonstrate that KGFR endocytosis on binding of the two alternative ligands, KGF or FGF10, is clathrindependent; however, once internalized the receptors follow two different intracellular endocytic pathways: while KGF targets the receptor to the lysosomal pathway, FGF10 induces KGFR recycling to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may block the sorting from early to late endosomes perturbing the actin cytoskeleton (Thomsen et al, 2000). More recently, however, it has been proposed that 16E5 affects the EGF endocytic trafficking altering the endosome fusion through a pH-independent and cytoskeletonindependent mechanism (Suprynowicz et al, 2010). In addition, it has been also demonstrated that E5 protein is able to form a complex with the EGFR and to enhance its ligand-dependent signaling by disrupting EGFR/c-Cbl interaction and consequently decreasing the ubiquitin-mediated receptor degradation (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…E5 induces anchorage-independent growth in culture (Leechanachai et al, 1992) and tumour formation in transgenic mouse models (Maufort et al, 2007), with expression detectable in human malignancies (Cavuslu et al, 1996;Hsieh et al, 2000;Sahab et al, 2012). E5 impairs endosomal maturation, thereby stabilizing epidermal growth factor receptor signalling, and leading to increased extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase activity Genther Williams et al, 2005;Leechanachai et al, 1992;Pedroza-Saavedra et al, 2010;Pim et al, 1992;Rodríguez et al, 2000;Straight et al, 1993;Suprynowicz et al, 2010;Tomakidi et al, 2000). However, understanding of the precise mechanism by which E5 mediates this is incomplete.…”
Section: Dna Virus Viroporinsmentioning
confidence: 99%